Educational Management of Darul Falah Pagutan Islamic Boarding School During the Covid-19 Pandemic - Ali Fikri, H. M.; Liswati, Liswati; Riinawati, Riinawati (International Journal of Education and Digital Learning (IJEDL), 2022)
Currently, the discussion about Covid-19 is still heating up in the community. The Covid-19 pandemic that has hit since the beginning of 2020 has had an impact on various sectors of life. Various sectors are required to adapt to the arrival of the pandemic as an effort to survive. One of the affected sectors is Islamic boarding schools. Islamic boarding school is an educational bench which emphasizes the side of religious education in everyday life. Islamic boarding schools have their own peculiarities and characteristics in the education system used. During this pandemic, the Darul Falah Islamic boarding school, Pagutan, as a gathering place for students from various regions, was also required to adapt to the pandemic. Policies continue to be negotiated as a form of defense during this pandemic. Management at the Darul Falah Islamic boarding school, Pagutan, such as management and learning systems must also be changed with new innovations and creativity developed for safety and goodness at this time. The emergence of a pandemic certainly raises many problems such as limited space and weakening of effective learning activities. Islamic boarding schools also apply management that is quite different from before, such as switching the teaching and learning process to online or limiting activities that cause crowds. However, activities and activities in Islamic boarding schools must continue to run stably with various considerations for the common good. The emergence of a pandemic certainly raises many problems such as limited space and weakening of effective learning activities. Islamic boarding schools also apply management that is quite different from before, such as switching the teaching and learning process to online or limiting activities that cause crowds. However, activities and activities in Islamic boarding schools must continue to run stably with various considerations for the common good. The emergence of a pandemic certainly raises many problems such as limited space and weakening of effective learning activities. Islamic boarding schools also apply management that is quite different from before, such as switching the teaching and learning process to online or limiting activities that cause crowds. However, activities and activities in Islamic boarding schools must continue to run stably with various considerations for the common good.